DETERMINAN VALUASI HARGA SAHAM DAN TINGKAT SUKU BUNGA PADA PERUSAHAAN PERDAGANGAN TERDAFTAR DI BURSA EFEK INDONESIA - Laurentine Novenita, Maria; Anwar, Choirul; JMV Mulyadi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This study aims to prove and explain that there is influence of Current Ratio, Dividend per Share, Return On Equity, Debt to Equity Ratio, Interest Rate SBI Moderate Current Ratio, Interest Rate SBI moderate Return On Equity to stock price at trading company in Indonesia Stock Exchange period 2011-2015.The research method used in this research is quantitative method, with multiple regression testing using classical assumption test before getting the best research model. Research variables used in this research are price as dependent variable, and Current Ratio, Dividend per Share, Return On Equity, Debt to Equity Ratio as independent variable and SBI Interest Rate rate as moderation. The number of purposive sampling as many as 16 companies as a sample and conducted for 5 years, so the total sample is 80. The results of this study indicate that there is a simultaneous relationship between Current Ratio, Dividend Share, Return On Equity, Debt To Equity Ratio, SBI Interest Rate moderate Current Ratio and Interest Rate SBI moderate Return On Equity to stock price, Adjusted R Square of 77.2% is explained by the independent variable that exists, the remaining 22.8% is influenced by other variables. Partially Current Ratio, Dividend Per Share, Debt To Equity Ratio influence significantly to stock price, this is indicated by level of significance that <0,05, while Return On Equity, Interest Rate SBI moderate Current Ratio and Interest Rate SBI moderate Return On Equity has no effect on stock price with significance level> 0,05.